Skip to content
= λf.(λx.f(xx))(λ.xf(xx))
= λf.(λx.f(xx))(λ.xf(xx))



Block or Report

Block or report MichaelNeas

Block user

Prevent this user from interacting with your repositories and sending you notifications. Learn more about blocking users.

You must be logged in to block users.

Report abuse

Contact GitHub support about this user’s behavior. Learn more about reporting abuse.

Report abuse


  1. 🦉Public speaking and blogs

    Swift 28 10

  2. framewerk Public

    🍎 developer docs flashcard app made with swiftUI

    Swift 6 2

  3. laboratory Public

    🧪 Programming challenges, demos, and practice

    Swift 8

  4. mikeneas Public

    Personal Website 🏔


  5. aviatodev Public archive

    Aviatodev 👩‍💻👨‍💻

    JavaScript 2 1

  6. hydra Public archive

    Open Source Prosthetic Arm 🦾

    Java 1 2

108 contributions in the last year

May Jun Jul Aug Sep Oct Nov Dec Jan Feb Mar Apr May Mon Wed Fri

Contribution activity

May 2022

Created 1 commit in 1 repository

Seeing something unexpected? Take a look at the GitHub profile guide.